Interrogating the Prospects and Challenges of State Policing System in Nigeria - Ikubanni, Oluwaseye Oluwayomi; Adeboye, Oluwaseye Thompson; Oyebanji, Aderemi Olubunmi; Oyebade, Alade Adeniyi; Aderibigbe, Oluwagbenga (JURNAL LEGALITAS, 2024)
The upsurge of insecurity in Nigeria questions the competence of the Nigerian Police Force under the auspice of the federal government to combat insecurity. Some concerns decentralizing the policing powers to states would offer potential benefits in curbing insecurity. This study was designed to interrogate the prospects and possible challenges of the state policing system in Nigeria and contribute to the discourse on security in a heterogeneous country like Nigeria. The study adopted a hybrid research methodology through a fusion of both doctrinal and non-doctrinal methods. Descriptive and analytical approaches were adopted to interpret empirical data collected through the distribution of 1,051 questionnaires to randomly selected respondents to ascertain the prospects and possible challenges of state policing in Nigeria. The study found that the current structure of the Nigerian Police Force can no longer guarantee the safety of the Nigerians. Furthermore, the synthesisation of empirical findings revealed that state policing has the prospect of competently combating insecurity in Nigeria but corruption, and lack of funding amongst others are possible challenges. The study therefore concluded by recommending the amendment of the current legal framework of policing in Nigeria to make way for decentralization.